Teknik Pemeriksaan Pelvis Judet View Pada Kasus Trauma Pelvis - Wahyuddin Wahyuddin; AR.Rakhmansyah Iskandar; Nurmi Febriani (Lontara Journal of Health Science and Technology, 2020)
Trauma is the most frequent cause of death in the general population after cardiovescular damage and cancer pade patients under yo years of age and trauma is the leading causes of death. One of the files of trauma is the pelvis. The study was conducted with the goal of explaning the judet view pelvis examination of the trauma pelvis with the studi literature approach. The research was carried out in march up to may. The spout of this study that pelvis inspection using judet method was a radio-graphic examination done to show the pelvis andevaluate the disorders of fractures, dislocation, tumors, etc. With the patient is disposed of in oblique position snd bearing optimal results in enforitating the diagnosis using judet method projection, it is already able to make the diagnosis known to the pelvis.